2005
DOI: 10.1016/j.fertnstert.2005.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Time to pregnancy and pregnancy outcome

Abstract: OBJECTIVE: To investigate whether the outcome of a pregnancy is related to the time required to achieve that pregnancy (TTP).DESIGN: The distribution of the TTP for pregnancies ending in multiple birth, early (before week 12) and late (weeks 12-28) miscarriage, stillbirth, and extrauterine pregnancy was compared to that of pregnancies ending in singleton birth. Furthermore, the distribution of the TTP for preterm singleton births was compared to that of fullterm singleton births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
3
33
0
1
Order By: Relevance
“…Previous studies have shown that polycystic ovarian syndrome patients have increased obstetric complications including higher rates of preeclampsia and gestational diabetes compared to other diagnoses [16] which may explain some of these differences. Prior studies in non-ART populations have also suggested that time-to-pregnancy can affect birth outcome [17]. Hypothetically, the longer it takes a woman to achieve pregnancy the more intractable her infertility might be.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that polycystic ovarian syndrome patients have increased obstetric complications including higher rates of preeclampsia and gestational diabetes compared to other diagnoses [16] which may explain some of these differences. Prior studies in non-ART populations have also suggested that time-to-pregnancy can affect birth outcome [17]. Hypothetically, the longer it takes a woman to achieve pregnancy the more intractable her infertility might be.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy per cent of the sexual cycles of multiparous female baboons are nonconceptive (Gesquiere et al, in press); that is, the female has a complete and apparently normal sexual cycle and mates repeatedly but does not conceive an offspring (interestingly, this value of 70% reflects a fecundability not dissimilar to women in industrialized societies, for whom median time to conception is between two and three cycles, reflecting a higher than 50% rate of cycling without conception; Tuntiseranee et al 1998;Axmon & Hagmar 2005). The frequency of nonconceptive cycles is much higher for adolescent female baboons (Gesquiere et al, in press).…”
Section: Stage 2: Allocating Mating Effortmentioning
confidence: 99%
“…The higher prevalence of these morbidities may relate to treatment, or indicate that subfertility predisposes to a higher risk for PTB and LBW. Whereas the prevalence of PTB and LBW is increased among women receiving treatment for subfertility (other than IVF), it also increased in untreated women having a prolonged time-to-pregnancy, suggesting that there may be factors that both decrease reproductive efficiency and increase the risk for adverse pregnancy outcomes, such as PTB and LBW (Joffe and Li, 1994;Basso and Baird, 2003;Axmon and Hagmar, 2005;Zhu et al, 2007;Allen et al, 2008;Romundstad et al, 2008).…”
Section: Introductionmentioning
confidence: 99%